PENERAPAN MEDIA PEMBELAJARAN BERBASIS VIDEO DENGAN PENDEKATAN PBL (PROBLEM BASED LEARNING) UNTUK MENINGKATKAN HASILBELAJAR SISWA PADA MATERI MANAJEMEN LIMBAH DISMK AL-BUKHORI - Ana Dwi Lestari; Haning Hasbiyati; Umi Nurjanah (JURNAL BIOSHELL, 2018)
This study aims to determine the increase of science learning result. The subjects of the study were all students of class XI. Data collection techniques use tests, observations, and documentation. In the implementation of this research, researchers use two cycles consisting of stages: planning, implementation, observation and reflection. Analysis data in this research using qualitative approach.            Learning takes two cycles, learning in cycle I and learning in cycle II. Both have media and method equations, but differ in learning materials. In the first cycle obtained the group activity completeness number that is equal to 75%. On the second cycle progressed well with the obtained figures mask activity group that is equal to 88. Activity of this group as a support to improve student learning outcomes.            Based on the results of classroom action research can be concluded Learning video media with Problem Based Learning model can improve student learning outcomes in materials science waste management subjects. This can be seen from the completeness of learning resultthat are classically achieved at each end of the cycle. In the first cycle obtained classical completeness number of 85%. Different with cycle II, in this cycle there is an increase of 90%. Ofthe total students of learning result already Reached the KKM that is >70.Keywords: Learning result, group activities, and Problem Based Learning